2014
DOI: 10.1371/journal.pone.0103971
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Transversus Abdominis Plane Block versus Continuous Wound Infusion for Post-Caesarean Analgesia: A Randomized Trial

Abstract: ObjectiveTo compare the analgesic effect of ultrasound-guided Transversus Abdominis Plane (TAP) block versus Continuous Wound Infusion (CWI) with levobupivacaine after caesarean delivery.MethodsWe recruited parturients undergoing elective caesareans for this multicenter study. Following written informed consent, they received a spinal anaesthetic without intrathecal morphine for their caesarean section. The postoperative analgesia was randomized to either a bilateral ultrasound guided TAP block (levobupivicain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 18 publications
0
39
1
1
Order By: Relevance
“…In this trial we didn't recorded any systemic toxicity (14,23,24) of local anesthetic in both arms of our trial like reported in prematurely terminated study of Chandon et al (14) due to occurrence of generalized convulsions in women in TAP group. Also, Weiss et al (24) reported two patients with convulsion after TAP block in cesarean delivery.…”
Section: Aydogmus Et Almentioning
confidence: 68%
See 2 more Smart Citations
“…In this trial we didn't recorded any systemic toxicity (14,23,24) of local anesthetic in both arms of our trial like reported in prematurely terminated study of Chandon et al (14) due to occurrence of generalized convulsions in women in TAP group. Also, Weiss et al (24) reported two patients with convulsion after TAP block in cesarean delivery.…”
Section: Aydogmus Et Almentioning
confidence: 68%
“…However, trial comparing local wound infiltration with TAP block after other abdominal surgery as cesarean section were few (12,13,14,15) . Also, meta-analysis of trial comparing TAP block with wound infiltration after abdominal surgery were few (18,19) .…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Chandon M. et al [38] In different abdominal surgeries, the effect of TAP Block has different effects on chronic post-operative pain. It may be due to the limited sample size of the patients, different surgical methods and different anatomy involved in different kind of surgery.…”
Section: Discussionmentioning
confidence: 95%
“…To date, a randomized clinical study compared the efficacy of the two techniques but the study was prematurely ended because of severe adverse events in the TAP block group [14].…”
Section: Page 5 Of 24mentioning
confidence: 99%